Des échelles pensées pour les enfants aux représentations spatiales produites par les enfants : enjeux politiques des imaginaires géographiques enfantins - Anne-Cécile Ott (Belgeo)
Building on my master’s degree research conducted with children from Alsatian nursery and elementary schools, I will question the differences between spatial representations produced for children and those produced by these actors. The analyses of the French Geography curriculum and of the handbooks, as well as he interviews with teachers and parents underline a strong focus on large-scale spaces. However the experimental methods I have developed to access children’s spatial representations show that small scales are also important in their geographical imaginaries, which span from local to global. Behind this discrepancy, political issues seem to be at stake. The Institutions present Geography in a very unpolitical way whereas children’s representations, and notably the fact that they often refer to small scales, are good indicators of their political and social awareness.